Point-Based Graphics (Morgan Kaufmann, 2007)
This book will present the latest research results in point-based computer graphics. After an overview of the key issues, affordable 3D scanning devices will be discussed and new concepts for the mathematical representation of point-sampled shapes will be presented. Then the authors will describe methods for high-performance and high-quality rendering of point models, including advanced shading, anti-aliasing, and transparency. The book will also present efficient data structures for hierarchical rendering on modern graphics processors (GPUs). In addition it will address methods for geometric processing, filtering and resampling of point models.The first book on a major development in graphics by the pioneers in the field:This technique allows 3D images to be manipulated as easily as Photoshop works with 2D images, Includes CD-ROM with the open source software program Pointshop3D for experimentation with point graphics